A review on individual reserving for non-life insurance / Kelly Chuah Khai Shin and Ang Siew Ling - Chuah, Kelly Khai Shin; Ang, Siew Ling (2021)
In recent decades, there has been great success with deterministic and stochastic unpaid claim reserving models based on triangles, such as those related to the chain ladder model (CLM). However, with the increased need for more accurate reserving models, taking advantage of the information embedded in individual claims data with appropriate claims development models are a promising alternative compared with the traditional aggregate loss development triangles. This research reviews on the development of using the individual claims data for reserving information.